Antibacterial Potential of Water Fractions of Hermetia Illucens Larves on Staphylococcus aureus and Prediction of Skin Permeability in Silico - Brilliant Kusuma; Aulia Nur Rahmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hermetia illucens (Black Soldier Fly/BSF) larvae are one of the animals utilised as a decomposer of organic waste and a source of protein-rich animal feed. Its metabolites, especially alkaloids, have various pharmacological and antibacterial activities. This study evaluated the potential of BSF larval water fraction extract (FABSF) as an antibacterial agent against acne-causing Staphylococcus aureus, as well as predicting skin permeability and irritation effects. Methods included secondary metabolite screening, antibacterial test (disc method), and microbial reduction measurement by UV-Vis spectrophotometer. In silico tests were used to predict skin permeability and potential irritation by analysing descriptively. Screening results showed FABSF was positive for alkaloids (Dragendorff and Wagner tests), flavonoids, and saponins, but no polyphenols or terpenoids were detected. The disc method test showed FABSF (40%, 80%, 100%) did not form a zone of inhibition. However, absorbance measurements showed a decrease in microbial counts by 85.47%, 86.89%, and 90.79% at each concentration. In silico assays identified compounds such as Butoctamide, N-(2-Hydroxyethyl)dodecanamide, and thane; (3Z,6Z)-5-imino-N,N,3-trimethyl-8-[5-[(4-methyl-1-bicyclo[4. 1. 1]octanyl)methyl]-2,3,3a,4,6,6a-hexahydropyrrolo[2,3-c]pyrrole-1-yl]nona-1,3,6,8-tetraen-4-amine suitable for topical preparations with good skin permeability and low risk of irritation.